2009
DOI: 10.4314/ajfand.v8i4.19200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of agricultural biodiversity on dietary diversity of preschool children in Matungu division, western Kenya

Abstract: Agricultural biodiversity encompasses the variety and variability of plants and animals that are necessary for food production and accessibility. Loss of agricultural biodiversity is taking place at a very high rate in Kenya. Many indigenous species that are not only nutritious, but also adapted to harsh conditions are now associated with poverty or backwardness. This profound change has great effect on preschool children in Kenya. Their diets are predominantly based on starchy staples, little or no animal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 4 publications
4
42
2
1
Order By: Relevance
“…Although some evidence suggests that agricultural biodiversity is strongly associated with dietary diversity [4,52–55], the socioecological settings and contexts in which this relationship exists are not fully established. In this study, socioeconomic status interacted with agricultural biodiversity on dietary diversity of a child, suggesting that the relationship between production diversity and dietary diversity scores differs according to the socioeconomic status of the child’s household.…”
Section: Discussionmentioning
confidence: 99%
“…Although some evidence suggests that agricultural biodiversity is strongly associated with dietary diversity [4,52–55], the socioecological settings and contexts in which this relationship exists are not fully established. In this study, socioeconomic status interacted with agricultural biodiversity on dietary diversity of a child, suggesting that the relationship between production diversity and dietary diversity scores differs according to the socioeconomic status of the child’s household.…”
Section: Discussionmentioning
confidence: 99%
“…Flow diagram of search strategy and selection process of articles on the contribution of biodiversity to human diets. Ekesa et al 2008;Roche et al 2008). The number of foods reported as part of habitual diets varied considerably.…”
Section: Biodiversity and Dietary Diversitymentioning
confidence: 96%
“…Of the studies which measured dietary diversity at the household or individual level: six reported a positive association with crop diversity (Ekesa et al 2008;Herforth 2010;Powell 2012;Jones et al 2012Jones et al , 2014Oyarzun et al 2013), one reported a positive association in one community but not another (Dewey 1981), and two reported no association (Torheim et al 2004;Remans et al 2011). Keding et al (2012) showed an association between diversity of vegetables cultivated and dietary diversity (number of food groups).…”
Section: Agrobiodiversity For Nutritionmentioning
confidence: 99%